2020
DOI: 10.1302/0301-620x.102b11.bjj-2020-0449.r1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scapular notching on clinical outcomes after reverse total shoulder arthroplasty

Abstract: Aims Scapular notching is thought to have an adverse effect on the outcome of reverse total shoulder arthroplasty (RTSA). However, the matter is still controversial. The aim of this study was to determine the clinical impact of scapular notching on outcomes after RTSA. Methods Three electronic databases (PubMed, Cochrane Database, and EMBASE) were searched for studies which evaluated the influence of scapular notching on clinical outcome after RTSA. The quality of each study was assessed. Functional outcome sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“…However, in some studies regarding aTSA, early baseplate loosening found on a radiological exam did not deteriorate in the long-term follow-up [ 2 , 5 , 9 , 12 , 26 ]. In cases of rTSA, scapular notching did not improve in the long-term follow-up, resulting in a significantly negative effect on the clinical outcomes [ 14 ]. Since our study did not have a long-term follow-up, further research will be needed to confirm the long-term prognosis of each treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some studies regarding aTSA, early baseplate loosening found on a radiological exam did not deteriorate in the long-term follow-up [ 2 , 5 , 9 , 12 , 26 ]. In cases of rTSA, scapular notching did not improve in the long-term follow-up, resulting in a significantly negative effect on the clinical outcomes [ 14 ]. Since our study did not have a long-term follow-up, further research will be needed to confirm the long-term prognosis of each treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A mechanical impingement between the humeral component and the inferior scapular neck and the glenoid were discussed to be responsible for scapular notching [ 3 , 6 , 41 ]. This mechanical impingement can lead to wear of the polyethylene insert of the humeral component and subsequently cause osteolysis of the surrounding bone [ 3 , 42 ]. However, the clinical significance of scapular notching is still a controversial topic.…”
Section: Implant Designmentioning
confidence: 99%
“…There has been some debate regarding the inferior tilt of the glenoid baseplate. However, considering the normal anatomy of the glenoid with a 5° superior tilt and the superior wear of cuff tear arthropathy, a 10° inferior tilt of the baseplate is recommended to prevent scapular notching [32,33]. A glenosphere with an inferior offset (inferiorly overhanging glenosphere) can also be used for inferior translation of the glenoid component [34][35][36][37].…”
Section: A a B Bmentioning
confidence: 99%